Consultation between Central and Local Authorities in Financial Matters in Serbia - Orlović, Slobodan; Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Financial autonomy is of crucial importance for the political automony within the vertical organisation of power. Local level of government seems to be in the most vunerable position, bearing in mind the flexibility of the constitutional framework in this area. The communication between different levels of government is an useful tool in searching for a balans between local needs and needs of public financial sector as a whole. The subject of this paper is the existance of normative and institutional preconditions for integovernmental dialogue between central and local levels of government in the Republic of Serbia. This question had been put into the wider social and political context which include the constitutional position of local self-government, the type of eceltoral system on the both levels as well as the degree of constitutional and political culture in our society. The results of research show that there are normative and institutional preconditions for intergovernmental dialogue in the constitutional system of the Republic of Serbia, but, in reality, there is still much space for developing of a such kind of cooperation.